(untitled) - H G Davies (London, 1997)
The book contains the material for mathematics syllabuses of the ONC/D courses in Engineering, Science Construction and Technology. Some Modern Mathematics such as Boolean Algebra and Ligic Circuits has been included to meet the requirements of the later syllabuses, but the main part of the book deals with Trigonometry, Calculus and Algebra. At the end of each chapter a Miscellaneous Exercise is included composed of questions from past examinations of the Regional Examining Boards, and a Revision exercises of similar questions is included at the end of the book. There are many examples and illustrations to aid the student, a great number of which show the application of Mathematics in Science and Engineering
Keywords: engineering mathematics